Effect of PZT particle size on the electromechanical coupling coefficient of 0-3 PZT-cement composites - Chaipanich A. (2014)
PZT-cement composites were produced using PZT ceramic of different particle size (3.8 μm to 620 μm). The effect of PZT particle size on the electromechanical coupling coefficient (Kt) of the composites was then investigated. The results showed that the particle size of PZT used to produce the composite has a noticeable effect on the Kt values. The electromechanical coupling coefficient was found to increase with the particle size of PZT used where Kt values are found to be at 16.1% and 20.5% for composites with median particle size of 3.8 μm and 620 μm respectively. Enhanced piezoelectricity can be explained when PZT ceramic particle increased since there would exist a more functioning ceramic (accompanying more PZT grains) and less contacting surfaces between the PZT ceramic and the cement matrix. These would lead to better piezoelectric properties of the composites.